Three-Dimensional Hand-to-Gland Combat: The Future of Endoscopic Surgery? - Nassimizadeh, A.; Muzaffar, S. J.; Nassimizadeh, M.; Beech, T.; Ahmed, S. K. (Journal of Neurological Surgery Reports, 2015)
Objective To compare two dimensional (2D), three-dimensional (3D) non–high-definition (HD), and 3D HD endoscopic surgical techniques.Methods We describe our initial operative experience with a novel 3D HD endoscopic endonasal approach involving a pituitary adenoma resection, provide a case series, and review the current literature. This is the first case in Europe using the new 3D HD endoscope.Results Although research evidence remains limited, there are no significant negative perioperative or postoperative outcomes when compared with 2D endoscopic techniques. In our experience the narrow operating corridors of endoscopic surgery cannot be addressed with 3D endoscopic techniques. The new 3D HD endoscope creates imaging quality similar to conventional 2D HD systems.Conclusion Three-dimensional endoscopic endonasal techniques provide an exciting new avenue, effectively addressing potential depth perception difficulties with current 2D systems.
Keywords: surgery; pituitary; three-dimensional; transsphenoidal; endoscope